小于胎龄儿生后早期肾脏功能初探 (Zhongguo Dang Dai Er Ke Za Zhi, 2017)
OBJECTIVE: To investigate the renal function of small-for-gestational-age (SGA) infants at the early stage after birth. METHODS: A total of 40 preterm SGA infants, 33 full-term SGA infants, 80 preterm appropriate-forgestational-age (AGA) infants, and 33 full-term AGA infants were included in this study. The following indices were compared between the SGA infants and AGA infants within 48 hours after admission:blood urea nitrogen (BUN), serum creatinine (SCr), estimated glomerular filtration rate (eGFR), blood pressure, urine volume per body weight, and proteinuria. RESULTS: The preterm SGA group had a significantly lower BUN level than the preterm AGA group (P < 0.05). However, there were no significant differences in SCr level, eGFR, and blood pressure between the two groups (P > 0.05). The full-term SGA group had a significantly higher SCr level and a significantly lower eGFR than the full-term AGA group (P < 0.05). However, there were no significant differences in BUN level and blood pressure between the two groups (P > 0.05). There was no significant difference in urine volume per body weight between the preterm SGA and preterm AGA groups (P > 0.05) and between the full-term SGA and full-term AGA groups (P > 0.05). There was no significant difference in the incidence of proteinuria between the preterm SGA and preterm AGA groups (P > 0.05). Proteinuria was not present in the SGA full-term and AGA full-term groups. CONCLUSIONS: SCr and eGFR can be used as the diagnostic indices for early renal damage of SGA infants. The renal function is worse in full-term SGA infants than in full-term AGA infants.